Soil-Structure Interaction of Retaining Walls under Earthquake Loads (Journal of Engineering, 2013)
The study is devoted to both static and earthquake response analysis of retaining structures acted upon by lateral earth pressure. Two main approaches were implemented in the analysis, namely, the Mononobe-Okabe analytical method and the numerical Finite element procedure as provided in the ready software ABAQUS with explicit dynamic method. A basic case study considered in the present work is the bridge approach retaining walls as a part of AL-Jadiriya bridge intersection to obtain the effects of the backfill and the ground water on the retaining wall response including displacement of the retaining structure in addition to the behavior of the fill material. Parametric studies were carried out to evaluate the effects of several factors such as vertical and horizontal components of the earthquake, maximum peak acceleration, angle of friction, damping ratio, height of the wall and groundwater level within the medium of fill. Three heights of retaining walls were considered for those above mentioned factors, these are (2.9m, 4.7m and6.7m). A comparison is made between the responses obtained on the basis of finite element analysis with those obtained using the Mononobe-Okabe method. It is found that the lateral wall responses obtained using the FE were larger than those calculated by the Mononobe-Okabe method for all heights of the retaining wall, it was also found that pore pressure of the ground water depends on the water flow through the backfill during the earthquake. The distribution of the dynamic earth pressure on the wall is nonlinear and depends on the earthquake ground acceleration in addition to the wall height and soil properties. Based on the numerical analysis and the results obtained from the parametric studies carried out, two expressions are proposed to evaluate the maximum lateral wall response in terms of wall height, soil properties and earthquake base excitation acceleration, and hence the dynamic earth pressure acting on the retaining structure.